Atmospheric Pressure Cold Plasma: A Friendly Environment for Dry Enzymes. Issue 24 (13th November 2018) - Fanelli, Fiorenza; Fracassi, Francesco; Lapenna, Annamaria; Angarano, Valeria; Palazzo, Gerardo; Mallardi, Antonia
Abstract: A comprehensive study of the interaction of cold atmospheric pressure plasmas (CAPs) with dry enzymes is conducted to identify the experimental conditions that allow preserving enzyme functionality. Glucose oxidase (GOx) dry deposits are exposed to dielectric barrier discharges fed with pure helium, helium–oxygen, and helium–ethylene mixtures. The GOx loses functionality upon exposure to He/O2 CAP due to dry etching. X‐ray photoelectron spectroscopy reveals that, in parallel with the ablation, there are modifications of the chemical structure of the surface of the enzyme deposit that decrease the etching rate and eventually lead to a "crust" with a strong resistance against the ablation, responsible of process termination. Interestingly, the customary conditions used for plasma‐enhanced chemical vapor deposition using helium–ethylene mixtures (applied voltage <1.1 kVrms and exposure time ≤10 min) are friendly for GOx. It is therefore possible to immobilize enzymes by overcoating with a plasma‐deposited thin film, fully retaining enzyme functionality. Abstract : The conditions used to deposit polyethylene‐like thin films by cold atmospheric pressure plasmas are friendly for the enzyme glucose oxidase that can be immobilized by overcoating fully retaining its functionality.